Olaparib in patients with metastatic castration-resistant prostate cancer with DNA repair gene aberrations (TOPARP-B): a multicentre, open-label, randomised, phase 2 trial. Issue 1 (January 2020) - Mateo, Joaquin; Porta, Nuria; Bianchini, Diletta; McGovern, Ursula; Elliott, Tony; Jones, Robert; Syndikus, Isabel; Ralph, Christy; Jain, Suneil; Varughese, Mohini; Parikh, Omi; Crabb, Simon; et al.
Summary: Background: Metastatic castration-resistant prostate cancer is enriched in DNA damage response (DDR) gene aberrations. The TOPARP-B trial aims to prospectively validate the association between DDR gene aberrations and response to olaparib in metastatic castration-resistant prostate cancer. Methods: In this open-label, investigator-initiated, randomised phase 2 trial following a selection (or pick-the-winner) design, we recruited participants from 17 UK hospitals. Men aged 18 years or older with progressing metastatic castration-resistant prostate cancer previously treated with one or two taxane chemotherapy regimens and with an Eastern Cooperative Oncology Group performance status of 2 or less had tumour biopsies tested with targeted sequencing. Patients with DDR gene aberrations were randomly assigned (1:1) by a computer-generated minimisation method, with balancing for circulating tumour cell count at screening, to receive 400 mg or 300 mg olaparib twice daily, given continuously in 4-week cycles until disease progression or unacceptable toxicity. Neither participants nor investigators were masked to dose allocation. The primary endpoint of confirmed response was defined as a composite of all patients presenting with any of the following outcomes: radiological objective response (as assessed by Response Evaluation Criteria in Solid Tumors 1.1), a decrease in prostate-specific antigen (PSA) of 50% or more (PSA50) from baseline, or conversion of circulating tumour cell count (from ≥5 cells per 7·5 mL blood at baseline to <5 cells per 7·5 mL blood). A confirmed response in a consecutive assessment after at least 4 weeks was required for each component. The primary analysis was done in the evaluable population. If at least 19 (43%) of 44 evaluable patients in a dose cohort responded, then the dose cohort would be considered successful. Safety was assessed in all patients who received at least one dose of olaparib. This trial is registered at ClinicalTrials.gov, NCT01682772 . Recruitment for the trial has completed and follow-up is ongoing. Findings: 711 patients consented for targeted screening between April 1, 2015, and Aug 30, 2018. 161 patients had DDR gene aberrations, 98 of whom were randomly assigned and treated (49 patients for each olaparib dose), with 92 evaluable for the primary endpoint (46 patients for each olaparib dose). Median follow-up was 24·8 months (IQR 16·7–35·9). Confirmed composite response was achieved in 25 (54·3%; 95% CI 39·0–69·1) of 46 evaluable patients in the 400 mg cohort, and 18 (39·1%; 25·1–54·6) of 46 evaluable patients in the 300 mg cohort. Radiological response was achieved in eight (24·2%; 11·1–42·3) of 33 evaluable patients in the 400 mg cohort and six (16·2%; 6·2–32·0) of 37 in the 300 mg cohort; PSA50 response was achieved in 17 (37·0%; 23·2–52·5) of 46 and 13 (30·2%; 17·2–46·1) of 43; and circulating tumour cell count conversion was achieved in 15 (53·6%; 33·9–72·5) of 28 and 13 (48·1%; 28·7–68·1) of 27. The most common grade 3–4 adverse event in both cohorts was anaemia (15 [31%] of 49 patients in the 300 mg cohort and 18 [37%] of 49 in the 400 mg cohort). 19 serious adverse reactions were reported in 13 patients. One death possibly related to treatment (myocardial infarction) occurred after 11 days of treatment in the 300 mg cohort. Interpretation: Olaparib has antitumour activity against metastatic castration-resistant prostate cancer with DDR gene aberrations, supporting the implementation of genomic stratification of metastatic castration-resistant prostate cancer in clinical practice. Funding: Cancer Research UK, AstraZeneca, Prostate Cancer UK, the Prostate Cancer Foundation, the Experimental Cancer Medicine Centres Network, and the National Institute for Health Research Biomedical Research Centres.